Intramuscular ketamine vs. escitalopram and aripiprazole in acute and maintenance treatment of patients with treatment-resistant depression: A randomized double-blind clinical trial - Cigognini, Marco Aurélio; Guirado, Alia Garrudo; Meene, Denise van de; Schneider, Mônica Andréia; Salomon, Mônica Sarah; Alexandria, Vinicius Santana de; Adriano, Juliana Pisseta; Thaler, Ana Maria; Fernandes, Fernando dos Santos; Carneiro, Adriana; Moreno, Ricardo Alberto (Frontiers in Psychiatry, 2022)
Objective: Ketamine, an N-methyl D-aspartate (NMDA) receptor antagonist, can promote rapid action in the management of individuals with treatment-resistant depression (TRD) at sub-anesthetic doses. However, few studies have investigated the long-term use of ketamine administered intravenously (IV) and intranasally (IN). We report the design and rationale of a therapeutic trial for assessing the efficacy, safety and tolerability of repeated dose intramuscular (IM) ketamine versus active treatment (escitalopram and aripiprazole) in TRD patients. Method: A comparative, parallel-group, randomized double-blind trial assessing the efficacy, safety and tolerability of acute (4 weeks) and maintenance (24 weeks) use of IM ketamine (0.75 mg/kg) versus active control (escitalopram 15 mg and aripiprazole 5 mg) in individuals with moderate-severe intensity TRD (no psychotic symptoms) with or without suicide risk will be conducted. Patients with TRD (18-40 years) will be randomized and blinded to receive ketamine IM or active treatment at a 1:1 ratio for 4 weeks (active treatment) and 24 weeks (maintenance treatment). Subjects will be assessed using clinical scales, monitored for vital signs (VS) after application of injectable medication, and undergo neuropsychological tests. The primary outcome will be changes on the Montgomery-Åsberg Depression Rating Scale (MADRS) during the course of the trial. Results: This study can potentially yield evidence on the use of IM ketamine in the treatment of depressive disorders as an ultra-rapid low-cost therapy associated with less patient discomfort and reduced use of medical resources, and can elucidate long-term effects on different outcomes, such as neuropsychological aspects. Conclusions: The trial can help promote the introduction of a novel accessible approach for the treatment of a complex disease (TRD) and also allow refinement of its long-term use.